2015
DOI: 10.1097/nen.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Both CD14-Positive and CD15-Positive Myeloid-Derived Suppressor Cell Subpopulations in the Blood of Patients With Glioma But Predominance of CD15-Positive Myeloid-Derived Suppressor Cells in Glioma Tissue

Abstract: Myeloid-derived suppressor cells (MDSCs), defined as CD33-positive major histocompatibility complex class II-negative cells, are increased in a variety of human tumors and are associated with immunosuppression. Myeloid-derived suppressor cells can be further subdivided into CD14-positive monocytic MDSC and CD15-positive granulocytic MDSC (polymorphonuclear MDSC) subpopulations. Here we analyzed MDSC subsets in the blood and tumor tissue of patients with glioma, including the most malignant variant, glioblastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 39 publications
7
111
1
Order By: Relevance
“…Our finding of elevated numbers of monocytic MDSCs in glioblastoma patients is consistent with a previous report that these cells represent a major subpopulation of MDSCs in the blood of glioblastoma patients (20). Additionally, it has been shown that patients with advanced cancer have high levels of blood neutrophilia (61), which we observed in glioblastoma patients as well.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of elevated numbers of monocytic MDSCs in glioblastoma patients is consistent with a previous report that these cells represent a major subpopulation of MDSCs in the blood of glioblastoma patients (20). Additionally, it has been shown that patients with advanced cancer have high levels of blood neutrophilia (61), which we observed in glioblastoma patients as well.…”
Section: Discussionsupporting
confidence: 93%
“…We did not find a significant difference in the number of monocytes between glioblastoma patients who were given steroids prior to resection at the time of blood draw and those not given steroids (Supplemental Figure 1B). Researchers have defined immune-suppressive neutrophilic and monocytic MDSCs based on their surface expression of CD33 + CD11b + CD14 − CD15 + and CD33 + CD11b + CD14 + CD15 − , respectively (20, 21). In the blood of glioblastoma patients, we identified three myeloid cell populations: the predominant monocytic subset of MDSCs (CD33 + CD11b + CD14 high CD15 − ), a minor population of neutrophilic MDSCs expressing CD33 + CD11b + CD14 low CD15 + , and CD11b + CD14 low monocytes (Supplemental Figure 1, C and D).…”
Section: Resultsmentioning
confidence: 99%
“…1). Moreover, this heterogeneous population is composed of cells defined as CD14 + monocytic MDSC (CD11b + CD33 + C14 + ) and CD15 + granulocytic MDSC (CD11b + CD33 + CD15 + CD14 – ) [4]. Human MDSCs commonly express Siglec-3/CD33 and lack lineage markers and HLA-DR, but heterogeneous expression of CD14 and CD15 suggests the presence of multiple subsets.…”
Section: Phenotypical and Molecular Characteristics Of Myeloid-derivementioning
confidence: 99%
“…In contrast, as shown in Figure 5 b , Aneustat very markedly reduced the numbers of FOXP3 + Treg cells (by >90%), thereby markedly increasing the ratio of intratumoral patient anticancer T cells to Treg cells in the Aneustat‐treated tissues. NK cells and MDSCs were identified by staining with NCR1 and CD33, respectively 35, 36, 37. As shown in Figure 6, the Aneustat‐treated tissues showed higher NCR1 + NK cell numbers compared to controls, whereas the MDSCs in the Aneustat‐treated tissues were lower in number than in the controls.…”
Section: Resultsmentioning
confidence: 95%